Process of Receiving and Disputing Empty Containers PT. Evergreen Shipping Agency Indonesia Medan - Reski Varezi; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
International shipping involves a joint operation between a country and its neighbors, often involving the handling of empty containers. This study aims to understand the process of empty container handling at Evergreen Shipping Agency Indonesia Branch Medan using field research, interviews, library research, and document analysis. Data collection methods include field observation, interviews, and surveys with staff. The study covers administrative tasks such as document verification, gate inspection, and container cleaning.